Gendering the practice turn in diplomacy. (September 2020) - Standfield, Catriona
International Relations has developed an exciting new research agenda on diplomatic practice, drawing largely on the theories of Pierre Bourdieu. However, it largely ignores Bourdieu's theory of patriarchy, as well as extensive feminist Bourdieusian analysis. These are analytical tools that can be used to understand how diplomacy reproduces itself as a masculinized field. They are 'practice theory' as well and should be incorporated into our research on diplomatic practice. My aims here are to recover feminist practice theory for a diplomatic studies audience and to indicate how we can develop an interdisciplinary research agenda on gender and diplomacy. The first part of the article provides an overview of practice theory in diplomatic studies and discusses Bourdieu's overlooked contributions regarding gender. I then use Bourdieu's 'thinking tools' of field, habitus and practice to examine diplomacy and gender using examples drawn from the literature, as well as from some primary sources. Throughout, I show how feminist sociologists have developed his ideas to create sophisticated approaches to studying the persistence of patriarchy. This does not capture all the ways in which diplomacy is gendered, but these tools reveal the limitations in our current understanding of diplomatic practices. I conclude with suggestions for future interdisciplinary research that takes gender seriously.